2012
DOI: 10.1158/0008-5472.can-12-1248
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Signaling Is a Novel Therapeutic Target in Tamoxifen-Resistant Breast Cancer Aberrantly Activated by PI3K/AKT Pathway

Abstract: Endocrine resistance is a major challenge in the management of estrogen receptor (ER)-positive breast cancers. Although multiple mechanisms leading to endocrine resistance have been proposed, the poor outcome of patients developing resistance to endocrine therapy warrants additional studies. Here we show that noncanonical Hedgehog (Hh) signaling is an alternative growth promoting mechanism that is activated in tamoxifen-resistant tumors. Importantly, phosphoinositide 3-kinase inhibitor/protein kinase B (PI3K/A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
154
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(167 citation statements)
references
References 40 publications
6
154
2
5
Order By: Relevance
“…A number of developmental signaling pathways, including Notch, PI3K/Akt, Wnt/β-catenin, Hedgehog and p53, [49][50][51] have been shown to have central roles in mammary tumorigenesis and stem cell biology. Activation of the PI3K/ Akt pathway has emerged as a central feature of EMT.…”
Section: Figure 4 Continuedmentioning
confidence: 99%
“…A number of developmental signaling pathways, including Notch, PI3K/Akt, Wnt/β-catenin, Hedgehog and p53, [49][50][51] have been shown to have central roles in mammary tumorigenesis and stem cell biology. Activation of the PI3K/ Akt pathway has emerged as a central feature of EMT.…”
Section: Figure 4 Continuedmentioning
confidence: 99%
“…140 The Hh signaling cascade is initiated by Hh binding to the 12-transmembrane receptor Patched 1, which relieves its inhibition on Smoothened (Smo), culminating in the nuclear localization of DNA-binding Gli transcription factors in target cells. 141 Several research groups reported that Hh signaling is aberrantly activated in various cancer types, including colon, 142 brain, 143 and breast, 144 liver, 145 lung, 146 and ovarian 147 cancer. Therefore, targeting Hh signaling pathway may provide an effective therapeutic approach in the treatment of various cancers.…”
Section: Hedgehog Signaling Pathwaymentioning
confidence: 99%
“…Menin recruits PRMT5 to the GLI1 promoter to lay down the H4R3me2 repressive mark in a Hedgehog signalingindependent manner 42 and a recently identified noncoding RNA induces H3K27me3 at the GLI1 promoter, thereby reducing RNA polymerase II recruitment. 43 GLI1 has frequently been implicated in cancer cell therapy resistance through decreased chemotherapy and radiotherapy responsiveness [44][45][46][47][48] and increased expression of cell surface drug transporters. [49][50][51] Recently, GLI1 was shown to drive resistance of AML cells to ribavirin and cytarabine through UGT1A-dependent glucuronidation of the compounds and inhibition of GLI1 with GANT61 restored sensitivity.…”
Section: Discussionmentioning
confidence: 99%